MATHEMATICAL MODELLING OF BIOAEROSOL TRANSFER IN THE ATMOSPHERE NEAR A LARGE INDUSTRIAL CENTER TAKING INTO ACCOUNT HETEROGENEITY OF TEMPERATURE AND HUMIDITY - Shvarts, K.G.; Shvarts, Y.A.; Shklyaev, V.A.; Balandina, S.Y.; Semerikov, V.V. (Perm Federal Research Centre Journal, 2017)
The paper presents the main results of a study of the spread of micromycetes from a natural source in the lower atmosphere in the neighborhood of Perm under the influence of temperature inhomogeneity and humidity of the underlying surface. In the considered rectangular area of 40 by 50 km five types of surface roughness were identified. Based on sample collection in the area called Kamskaya Dolina in close proximity to the perinatal center in the laboratory of "Bactericide" (PGU) 15 genera of fungi were identified in 2014, many species of which are known as pathogens of plants. Cladosporium was found as the leader of micromycetes with the highest concentration of spores, which come out in the summer. On the basis of the local-equilibrium approach equations of the mathematical model are derived. They are derived by averaging across the layer of the initial three- dimensional equations of velocity, thermal conductivity and humidity, describing mesoscale atmospheric processes, as well as the equation of living impurity transfer. The possibility of establishing local monitoring systems of bioaerosols on the basis of the developed model is evaluated. The necessary basic meteorological and microbiological elements and parameters of the problem are determined. The results of numerical calculations of the propagation of spores from a point source near Kamskaya Dolina in Perm with and without consideration of its reproduction, taking into account the local air movements arising due to its temperature inhomogeneities, using a grid method are presented. The spatial grid spacing is 200 meters. The calculations were performed for a variety of weather conditions. In winter bioaerosol behaves like a passive impurity - a weak heterogeneity of the underlying surface covered with snow, almost no effect on the movement of air. In summer, the temperature heterogeneity of the underlying surface forms local motion of air, affecting the direction of wind and increasing its velocity. The account of the reproduction of mold significantly increases their maximum concentration in the lower layer of the atmosphere.